Perspectives for Lithuanian Social Insurance System - Poškutė, Virginija (Ekonomika, 1999)
It has been four years since the Law on National Social Insurance Pensions came into force. It is now possible to make some conclusions about the System’s problems and it’s likely future development. This article analyses the long-term (1999-2030) development of the National Social Insurance System. The System’s forecast development is based on a modified model constructed by the World Bank researchers in 1993-1994. The earlier model required some major modifications in order to serve for the forecasting purposes. Since the model was first constructed: a) new demographic data has become available; b) macroeconomic inputs were adjusted to reflect the country’s current situation; c) calculation of old age pension benefits was modified to conform with the new legal environment; d) calculation of the other pension benefits was modified; and e) two new categories of widows and orphans pensions were included into the model. Two possible scenarios for the System’s budget are presented in the article: 1) The pension age remains as it is specified in current legislation, 2) The pension age is raised to 65 for both men and women.